2001
DOI: 10.1029/2000ja000248
|View full text |Cite
|
Sign up to set email alerts
|

Multisatellite comparisons of the radiation belt response to the Geospace Environment Modeling (GEM) magnetic storms

Abstract: Abstract. We present a compilation of observations of relativistic radiation belt electrons during the four Geospace Environment Modeling (GEM) storms from instruments on 10 separate spacecraft. While these four magnetic storms have very different solar wind and magnetospheric conditions, there are several characteristics of the relativistic electron response which are applicable to all four storms. We find that although the evolution of the spectral shape of the electrons at a specific L shell does not vary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
3
23
0
1
Order By: Relevance
“…Our previous studies have shown evidence for local peaks but were limited by the range of L-shells (e.g. McAdams et al 2001;Chen et al 2005) or by high spacecraft latitudes that limited pitch angle coverage (e.g., Selesnick and Blake 1997;Green and Kivelson 2004). The ECT particles suite (plus magnetic field observations) will provide phase space density gradients over the full range of μ, J , and L * values that are crucial to understand belt dynamics.…”
Section: Ect Closure On Science Objective #1 Questionmentioning
confidence: 99%
“…Our previous studies have shown evidence for local peaks but were limited by the range of L-shells (e.g. McAdams et al 2001;Chen et al 2005) or by high spacecraft latitudes that limited pitch angle coverage (e.g., Selesnick and Blake 1997;Green and Kivelson 2004). The ECT particles suite (plus magnetic field observations) will provide phase space density gradients over the full range of μ, J , and L * values that are crucial to understand belt dynamics.…”
Section: Ect Closure On Science Objective #1 Questionmentioning
confidence: 99%
“…The commonly used method is to convert the flux observed at fixed energy to phase space density at constant first, second and third adiabatic invariants. Many papers have been written on this topic recently Blake, 1997, 2000;Hilmer et al, 2000;McAdams et al, 2001;Green and Kivelson, Y. Shi et al: Features of energetic particle radial profiles 2004; Onsager et al, 2004;Taylor et al, 2004;Iles et al, 2006;Chen et al, 2005Chen et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The review by Friedel et al (2002) includes all these mechanisms for acceleration. The main candidates are based on either local diffusion due to particle interactions with waves (Temerin et al, 1994;Shprits et al, 2008;Reeves et al, 2009;Omura et al, 2007;Horne et al, 2005;Summers and Thorne, 2003;Summers et al, 1998Summers et al, , 2002Summers et al, , 2004Albert, 2003Albert, , 2005 or radial diffusion (Falthammar, 1968;Schulz and Lanzerotti, 1974;Hilmer et al, 2000;Ingraham et al, 2001;McAdams et al, 2001). …”
Section: Introductionmentioning
confidence: 99%